Cuidado de bebê com cardiopatia congênita: estudo de caso sobre a interação e vínculos entre humanos e tecnologias - Gondim, Andressa Alencar (2024)
The beginning of life records the subject’s first experiences in the world, which will leave perceptions that will be present for a lifetime, interfering with our ways of living. It is through contact with others, more specifically the figure of the caregiver, that the structuring of the Self occurs, including capabilities and illnesses. The foundation of psychic health and life of an adult, according to Winnicott (1948), in the first years of baby care in a positive environment is where the complex processes of forming a “self” for the baby happens. Therefore, early experiences are crucially important in the structuring of the Self. Referring to babies with complex congenital heart disease, the caregiver-baby/child relationship is constantly influenced by hospital interventions, often beginning at the baby’s birth - when the diagnosis is made during the firsts newborn care – and continues throughout life, as this diagnosis requires longitudinal monitoring. Thus, the maintenance of life relies on medical equipment, machines that ensure the functioning of the baby’s body with congenital heart disease, as well as on the care provided directly by humans. The perception of the cyborg, as introduced by Haraway (2017), makes us consider how humans and machines have become interdependent, which applies to babies whose lives depend on hospital machinery. Therefore, using the Esther Bick observation method, this work sought to understand how bonds between humans and non-humans (machines) are estabilished in the relationship with a baby diagnosed with congenital heart desease. A case study was conducted with a baby admitted to a Pediatric ICU. It was observed that parents are responsible for creating an embracing atmosphere of affection that ensures the baby’s Self development, through interpretations of the baby’s expressions, as well as signals from the machines, giving shape to their subjectivity. Technology has not completely replaced humans, as it cannot create the nuances and emotional bonds necessary for the baby’s subjective development, but it intertwines with the bond established with parents and professionals, as well as serving as a tool for the patientbaby- child to connect with the world outside the hospital, through social networks.